2023
DOI: 10.1002/dad2.12500
|View full text |Cite
|
Sign up to set email alerts
|

Remote and in‐clinic digital cognitive screening tools outperform the MoCA to distinguish cerebral amyloid status among cognitively healthy older adults

Louisa I. Thompson,
Zachary J. Kunicki,
Sheina Emrani
et al.

Abstract: INTRODUCTIONWe evaluated the accuracy of remote and in‐person digital tests to distinguish between older adults with and without AD pathological change and used the Montreal Cognitive Assessment (MoCA) as a comparison test.METHODSParticipants were 69 cognitively normal older adults with known beta‐amyloid (Aβ) PET status. Participants completed smartphone‐based assessments 3×/day for 8 days, followed by TabCAT tasks, DCTclock™, and MoCA at an in‐person study visit. We calculated the area under the curve (AUC) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…54 Another remote digital assessment -the M2C2 Prices task as part of the NIH Mobile Toolbox -distinguishes A+ versus A-participants better than the MoCA. 52 Our group has previously shown that a one-time administered SLS discriminates between A+ and A-groups, as well as A+T+ and A-T-groups in a predominantly CU sample. 11 Mayo Test Drive & Imaging Biomarkers -20…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…54 Another remote digital assessment -the M2C2 Prices task as part of the NIH Mobile Toolbox -distinguishes A+ versus A-participants better than the MoCA. 52 Our group has previously shown that a one-time administered SLS discriminates between A+ and A-groups, as well as A+T+ and A-T-groups in a predominantly CU sample. 11 Mayo Test Drive & Imaging Biomarkers -20…”
Section: Discussionmentioning
confidence: 87%
“…31 To date, most of these remote digital assessments rely on multiple assessments, either once per day over several days (e.g., Boston Remote Assessment for Neurocognitive Health; BRANCH), 51 or multiple times per day over several days (e.g., Mobile Monitoring of Cognitive Change; M2C2). 52 Performance on BRANCH has robust associations with the PACC5 as well as associations with cortical amyloid and entorhinal tau deposition, 51 with diminished seven-day practice effects on BRANCH linked to increased levels of amyloid and declines on the PACC5 over one year in CU individuals. 53 Similarly, diminished practice effects on C3 over a three month period have been associated with greater amyloid and tau burden as well as steeper annual decline on the PACC5.…”
Section: Discussionmentioning
confidence: 99%
“… 19 , 20 , 21 , 22 , 23 , 24 Furthermore, this work showed that remote and unsupervised assessments can support the identification of mild cognitive impairment (MCI) patients in a memory clinic setting 25 and potentially even β‐amyloid (Aβ) positive but cognitively unimpaired (CU) participants. 19 , 26 , 27 The aim of the present study was to evaluate the feasibility and usability of unsupervised and remote digital memory assessments, their construct validity in reference to traditional neuropsychological assessments, their retest reliability, and their relationship with fluid and imaging biomarkers of AD. To that end, we implemented two non‐verbal visual memory tasks based on recent insights into the functional anatomy of episodic memory, available on the neotiv digital platform ( https://www.neotiv.com/en ), 21 , 24 in a subset of the Swedish BioFINDER‐2 study.…”
Section: Introductionmentioning
confidence: 99%
“…A shift from paper and pencil to digital cognitive assessment tests is highly advantageous, particularly for Nigeria experiencing rapid demographic aging and widespread cognitive screening (Thompson et al, 2023 ). Digital tests improve efficiency, accuracy, and accessibility, making the assessment process smoother and reducing logistical challenges and the subjective nature of current standardized cognitive assessment methods (Staffaroni et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%